Efektifitas Pemberian Rebusan Daun Salam dengan Senam Hipertensi Pada Lansia Hipertensi untuk Menurunkan Tekanan Darah - Auliya Sina Mugna; Siti Juwariyah; Mamat Supriyono (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Older adults are someone who is over 60 years old, which is the final stage of the development of human life, or someone who is starting to enter the stage of the aging process. This study aimed to determine the difference in effectiveness of giving bay leaf decoction with hypertension exercise to older adults with hypertension to reduce blood pressure in Karangayu, Semarang Barat, before and after the intervention. This research method used quasi-experimental pre-and post-tests for two intervention groups, 1 and 2. The sampling technique used was non-probability sampling on 74 respondents, using pre-test and post-test observation sheets with SOP for boiled bay leaves and SOP for hypertension exercises. This study showed that the average blood pressure before being given the bay leaf decoction intervention in group 1 was 89.2% with severe pain. In contrast, the average blood pressure after being given bay leaf decoction intervention was 86.5%, with mild blood pressure. For group 2, the average blood pressure before being given the hypertension exercise intervention was 94.6% with severe pain. Meanwhile, the average blood pressure after the hypertension exercise intervention was 75.7% with mild blood pressure. The results of the marginal homogeneity test obtained a P value of 0.001 (<0.05), meaning that there was a significant difference in mean between the pre-test and post-test, which affected the effect of giving bay leaf decoction with hypertension exercise on blood pressure in the older adults. Advice to health services, such as Posbindu (Pos Pembinaan Terpadu), on how to provide non-drug treatment with bay leaf decoction and hypertension gymnastics, which means physical exercise and traditional medicine, as part of training for Posbindu officers in secondary prevention services for high blood pressure in older adults.